Long-term prognosis of hematogenous vertebral osteomyelitis: Mortality, quality of life, and pain - Kokabu, Terufumi; Takahata, Masahiko; Ishiguro, Nobuhisa; Iwasaki, Norimasa (Journal of orthopaedic science : official journal of the Japanese Orthopaedic Association, 2017)
Hematogenous vertebral osteomyelitis (HVO) has a generally favorable prognosis if appropriate treatment is initiated in its early phase; however, some intractable cases with HVO can develop neurological impairment as well as spinal deformity during the course of treatment and these sequelae may lead to impaired quality of life (QOL). In this study, we aimed to evaluate the long-term relapse rate, mortality, and QOL of patients with HVO. In this retrospective case series study, medical records of 60 patients with HVO with a mean follow-up period of 8 years (5–23 years) were reviewed to assess demographic data, details of infection, and clinical course. Mortality rate was assessed using a Kaplan–Meier plot. QOL was measured using the EuroQol 5 Dimension (EQ-5D) questionnaire and residual pain using a numeric rating scale (NRS). HVO relapsed in 4 of 60 patients (7%). Overall 5-year survival rate in 60 patients with HVO was 85%. The factors associated with increased mortality were malignant tumor, diabetes mellitus, chronic use of glucocorticoids, and drug-resistant strains of staphylococcus. Female-to-male ratio, NRS, prevalence of neurological impairment were significantly higher in patients with low EQ-5D score (poor health) compared to those with high EQ-5D score (good health). Patients with HVO have shorter life expectancy if they have malignancy, diabetes mellitus, chronic use of glucocorticoids, and a history of drug-resistant strains of staphylococcus infection. Female gender, residual neurological defects and persistent back pain are associated with impaired QOL in patients with HVO.